Character-based leadership in improving guest service quality at premiere hotel tegal - Putriyanti, Tiara Diva; Rohmah, Nur; Asshofi, Izza Ulumuddin Ahmad (Surya Hijau Manfaat, 2024)
A leader has good character, unique qualities, habits and personality that make him the characteristics of a leader. Leadership is the process of directing and influencing the activities of people in a group. Leadership means involving other people, especially subordinates or staff who are led. A leader's problems usually arise from satisfaction with the quality of service provided to hotel guests. A leader must be able to adapt to surrounding circumstances and control them. The aim of this research is that a leader can develop leadership qualities that will help adjust the quality of hotel guest services and make the value of the hotel known to more people. Service quality includes the punctuality provided by the hotel to guests in accordance with expectations to meet needs. The method used in this article is qualitative. The results of this research are that characters-based leadership are able to improve the quality of service to hotel staffs to own the sense of self-confidence needed to provide quality hotel services to guests.